1.Rozwiąż równania.
a) 3(x-4)-4(2x-7)=2(x+5)
b) 2(2x-3)+3(4-x)=-(x+1)
c) 2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
d) 6(x+1)+3(2-x)=2(2x-1)-(4-x)


2. Rozwiąż równania.
a) 2(x-7)-3(x+2)=4(x+3)+2(x-9)
b) -3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
c) -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
d) 6(4-x)+5(2x-5)=4(x-1)-3(4-x)

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-19T19:29:07+01:00
1.
a) 3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-7x=-6
x=6/7

b) 2(2x-3)+3(4-x)=-(x+1)
4x-12+12-3x=-x-1
4x-3x+x=-1+12-12
2x=-1
x=-1/2

c) 2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2-6-12
-3x=-26
x=8,66

d) 6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-6-12
-2x=-6/:(-2)
x=3

2.
a) 2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=12-18+14+6
-7x=14/:(-7)
x=-2
b) -3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=-8+72+18+48
-26x=130/:(-26)
x=-5


c) -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-8x+3x+4x-8x=-16+15+6+4
-9x=9/:(-9)
x=-1


d) 6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x=-15/:-3
x=5
13 3 13
2010-03-19T19:31:43+01:00
1.
a) 3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-7x=-6
x=6/7

b) 2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
4x-3x+x=-1+6-12
2x=-7
x=-7/2

c) 2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
-3x=10
x=-10/3

d) 6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-6-6
-2x=-18
x=9


2.
a)2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=12-18+14+6
-7x=14
x=-2

b) -3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=-8+72+18+48
-26x=130
x=-130/26

c) -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-8x+3x+4x-8x=-6+4+16-15
-9x=-1
x=1/9

d) 6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x=15
x=-5
8 3 8
2010-03-19T19:35:19+01:00
Zadanie1
a)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x= 10+12-28
7x=-4/7
x=4/7
b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
4x-3x+x=-1+6-12
2x=5/2
x=5/2
x=2,5
c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
-3x=10/(-3)
x=-10/3
x=31/3
d) 6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-6-6
-2x=-18/(-2)
x=9
zadanie2
a) 2 (x-7) -3(x+2)= 4 (x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=12-18+14+6
-7x=14
x= - 2
b) -3(x+6)-6(2x+8) = -2 (4-x)+ 9 (x+8)
-3x-18-12x-48= -8 + 2x +9x+72
-3x-12x-2x-9x= -8-72+18+48
-26x = -14
x=14/16
c) -8(x+2)+3(x+5)= -2 (2x+3) +4 (2x-1)
-8x-16 +3x+15= -4x - 6 + 8 x-4
-8x+3x+4x-8x=-6-4+16-15
7x=-9
x= - 9/7
d) 6(4-x) +5 (2x-5)= 4 (x-1) -3 (4-x)
24-6x+10x-25 = 4x -4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x= - 15
x= 5



2 3 2